2022
DOI: 10.1177/00187208211053460
|View full text |Cite
|
Sign up to set email alerts
|

Drivers’ Performance in Non-critical Take-Overs From an Automated Driving System—An On-Road Study

Abstract: Objective The objective of this semi-controlled study was to investigate drivers’ performance when resuming control from an Automated Driving System (ADS), simulated through the Wizard of Oz method, in real traffic. Background Research on take-overs has primarily focused on urgent scenarios. This article aims to shift the focus to non-critical take-overs from a system operating in congested traffic situations. Method Twenty drivers drove a selected route in rush-hour traffic in the San Francisco Bay Area, CA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Overall, the non-critical average take-over time of 5.62 seconds we found, is between an on the road driving study reporting 2.70 and 5.50 seconds (Naujoks et al, 2019) and a similar study reporting an average of 8.70 seconds (Rydström et al, 2022). These results align well with the typical 6 seconds drivers needed to take back control from automation when engaged with a non-driving related task in a simulator study (Eriksson & Stanton, 2017b).…”
Section: Discussionsupporting
confidence: 82%
“…Overall, the non-critical average take-over time of 5.62 seconds we found, is between an on the road driving study reporting 2.70 and 5.50 seconds (Naujoks et al, 2019) and a similar study reporting an average of 8.70 seconds (Rydström et al, 2022). These results align well with the typical 6 seconds drivers needed to take back control from automation when engaged with a non-driving related task in a simulator study (Eriksson & Stanton, 2017b).…”
Section: Discussionsupporting
confidence: 82%
“…In both studies, drivers managed to transition back to manual driving in response to TORs. However, Rydström et al [17] reported take-over times up to 25 s, whereas Naujoks et al [16] only report take-over times up to 10 s. The likely explanation behind the longer take-over times in [17] is that the participants had no prior experience of the TOR and deactivation strategy prior to the test, while the participants in [16] had practiced beforehand.…”
Section: Need To Validate Previous Findings In Real Trafficmentioning
confidence: 93%
“…Therefore, there is a need to extend current findings (from the virtual environment involving critical scenarios) with studies conducted in real traffic in which drivers are given more than 7 s to deactivate AD. To the knowledge of the authors, only two studies have investigated drivers' responses to TORs during AD (hands-free driving allowed) in real traffic and under noncritical conditions (see, [16], [17]). Both these studies allowed participants to engage in NDRTs (as a manipulated variable in [16] and as voluntary engagement in [17]).…”
Section: Need To Validate Previous Findings In Real Trafficmentioning
confidence: 99%
See 1 more Smart Citation